Expression of calpastatin hcast 3-25 and activity of the calpain/calpastatin system in human glioblastoma stem cells: possible involvement of hcast 3-25 in cell differentiation - Spinelli, Sonia; Barbieri, Federica; Averna, Monica; Florio, Tullio; Pedrazzi, Marco; Tremonti, Beatrice F.; Capraro, Michela; De Tullio, Roberta (Frontiers in Molecular Biosciences, 2024)
Glioblastoma (GBM) is the most malignant brain tumor, characterized by cell heterogeneity comprising stem cells (GSCs) responsible for aggressiveness. The calpain/calpastatin (calp/cast) proteolytic system is involved in critical physiological processes and cancer progression. In this work we showed the expression profile of hcast 3-25 (a Type III calpastatin variant devoid of inhibitory units) and the members of the system in several patient-derived GSCs exploring the relationship between hcast 3-25 and activation/activity of calpains. Each GSC shows a peculiar calp/cast mRNA and protein expression pattern, and hcast 3-25 is the least expressed.Differentiation promotes upregulation of all the calp/cast system components except hcast 3-25 mRNA, which increased or decreased depending on individual GSC culture. Transfection of hcast 3-25-V5 into two selected GSCs indicated that hcast 3-25 effectively associates with calpains, supporting the digestion of selected calpain targets. Hcast 3-25 possibly affects the stem state promoting a differentiated, less aggressive phenotype.